AKSI SOSIAL KOMUNITAS NELAYAN CANTRANG TERHADAPKEBIJAKAN LARANGAN PENGGUNAAN ALAT PENANGKAPAN IKAN - Ambarwati, Aulia Siti; Adi, Isbandi Rukminto (UI Scholars Hub, 2019)
This research describes the existence of interventions at the community level through social action / community action carried out by the cantrang fishing community in Tasikagung Village, Rembang Regency. This action is an effort by the cantrang fishing community to fight for their welfare after the issuance of a policy on the prohibition on the use of cantrang type fishing gear through the Minister of Maritime Affairs and Fisheries Regulation of the Republic of Indonesia. This research is a study that uses a qualitative approach, with the type of research descriptive. The results of this study show that the change in living conditions in the cantrang fishing community, as well as the differences in perceptions between the fishermen and the government, are factors that encourage cantrang fishing communities to hold confrontational protests through demonstrations, roadblocks, and negotiations. The groups or stakeholders involved in this action include the communities that have work related to cantrang vessels